Analisis Kelas Massa Batuan Terhadap kestabilan Lereng Bendungan Lolak Menggunakan Metode Rock Mass Rating - Muarif, Fahmy Idris; Maryati, Sri; Hutagalung, Ronal (Universitas Negeri Gorontalo, 2022)
The process of displacement or movement of slope stability constituent materials followed by the sedimentation process of the deposited material is a landslide event. The negative impact of the landslide if it occurs in residential areas, can cause material and infrastructure losses, or economic losses in the affected area if the landslide products can cover the road access. The purpose of this study was to determine the level of rock mass and its effect on slope stability, and to determine the rock mass quality of the study area. The research area is located in Lolak Dam. Based on the results of the analysis carried out, the conclusion is that the observations starting from station 1, station 2, station 3, and station 4 show moderate-good rock strength. The condition of the discontinuity shows continuity of less than 1 meter, the aperture of discontinuity are open to a bit wide, with varying roughness, namely coarse, and slightly coarse, with the infilling material calcite veins. The level of weathering starts from weathered to very weathered. Groundwater conditions are dominated by discontinuities that have a dry level. Based on the discontinuity characteristic, station 1 has good rock mass class, station 2 has medium rock mass class, station 3 has medium rock mass class, and station 4 has good rock mass class. this value can be used as a reference value for the next stage of decision making regarding the strengthening of the slopes in the study area.